(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
This research aims to explain the complicated interplay between the ideas of pride and revenge in Joe Edgar’s famous literary work, "The Cask of Amontillado". Pride, as a human emotion, is widely considered as the most heinous of sins, because of its relationship with the original sin of Adam and Eve, which led to their expulsion from the Garden of Eden. Therefore, exploring the theme of pride and its disastrous consequences in Edgar’s work holds significant academic merit. In the famous narrative The Cask of Amontillado which written by the well- known author Edgar Allan Poe, the theme of revenge is manifested through the sinful actions of Montresor and Fortunato. The latter, in his arrogance, regularly insults Montresor, who then endeavors to revenge himself. The story reveals the cunning manipulation of Fortunato’s pride, leading him to his eventual death, with the lure of tasting Amontillado from an imaginary cask. The masterful portrayal of human weaknesses and the consequences of unrestrained pride make this story a timeless classic in the kingdom of literature. The human desire for revenge has long been a powerful force driving actions throughout history. Countless battles have been waged, and wars have been fought, all in the name of seeking revenge. The Cask of Amontillado serves as a main example of how one’s pride can be useful to fulfill another’s demonic designs for revenge. Montresor exploits Fortunato’s sense of superiority to exact his dark, vengeful desires, showcasing the intricate and often unpredictable nature of human motivation.